Design of creative virtual spaces through the use of a web application during the educational process about bank savings - Salas-Rueda, Ricardo-Adán; Alvarado-Zamorano, Clara (Creativity Studies, 2022)
The aim of this quantitative research is to design, build and analyze the use of the web application for the teaching-learning process on bank savings. This web application builds creative educational virtual spaces where students learn and analyze the mathematical procedure related to monthly interest rate, initial balance, final balance, interest and savings account. Also, data simulation of the web application for the teaching-learning process on bank savings allows that students have an active role in the learning process through the interaction and control of the contents about bank savings. The ASSURE model facilitates the planning, organization and construction of the web application for the teaching-learning process on bank savings through the stages of analysis, setting, selection, use, requirement and evaluation. The participants are 43 students who took the Financial Mathematics course during the 2018 school year. The results of linear regressions (machine learning) indicate that the construction of creative educational virtual spaces through the web application for the teaching-learning process on bank savings influences positively the assimilation of knowledge about the bank savings, simple interest and financial mathematics. The decision tree technique identifies 3 predictive models about the use of the web application for the teaching-learning process on bank savings in the educational field. The implications of this research allow that teachers analyze the impact of information and communications technology during the realization of school activities. Therefore, educational institutions can promote the construction and use new technological tools. Finally, the web application for the teaching-learning process on bank savings is a web application that allows the construction of creative educational virtual spaces where students personalize the learning and have flexibility of time and space during the educational process on bank savings.